Breastfeeding Patterns as a Determinant of Fertility in the Province of East Nusa Tenggara, Indonesia (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Although the fertility rate in East Nusa Tenggara Province has decreased over the last 10 years, the birth rate is still higher than other provinces in Indonesia. Interestingly, the infertility index for breastfeeding in East Nusa Tenggara Province is the lowest compared to other provinces in Indonesia, which means that women of childbearing age in East Nusa Tenggara Province breastfeed their children with the longest breastfeeding period. Therefore, this study aims to determine the fertility decomposition and characteristics of breastfeeding mothers in East Nusa Tenggara Province in 2017. The data source of this study uses the results of the 2017 Indonesian Demographic and Health Survey (IDHS) using women of childbearing age who have given birth. The analysis used in this study included fertility decomposition analysis and continued with univariable, bivariable, logistic regression analysis. The results of this study indicate that breastfeeding as a proxy for infertility towards fertility in the province of East Nusa Tenggara has an index value (Ci) of 0.72 and after controlling for maternal characteristics variables, age, education and work status of mothers are the factors most related to breastfeeding behavior in East Nusa Tenggara in 2017. Promotion of good breastfeeding techniques and the benefits of breastfeeding needs to be improved in order to improve the quality of life of infants, spacing pregnancies and reduce the incidence of tengkes (stunting).